75+things about QC what to love, do and see in Quezon City - Lacuesta, Sarge; Lacuesta, Mookie Katigbak; Fernando, Regie; Brotonel, Ian (Lungsod Quezon, 2010)
This book aims to provide an overview of the many delights of Quezon city. There are feasts of every conceivable kind in QC, and we hope to take you through the city district by district, pleasure by pleasure -- be it a culinary treat, a historical monument, a museum, or a walk in a park. Each district has a character distinctly different from the next. Diliman and Tomas Morato, for example, are wildly different in texture and flavor even as they're practically neighbors on the map. As EB White wrote in "Here is New York", move a few blocks up or down QC and you find a new spectacle.